Pharmacokinetics of oral acyclovir (Zovirax) in the eye. Issue 3 (March 1984) - Hung, S. O.; Patterson, A.; Rees, P. J.
Abstract : Patients due for cataract extraction received 5 doses of 400 mg acyclovir (Zovirax) orally during the 24 hours prior to surgery. Aqueous humour levels of acyclovir (mean 3.26 microM) were well above the normal ED50 range for herpes simplex virus type 1, and showed a significant correlation with plasma concentrations (mean 8.74 microM). There was also a correlation between the age of the patient and the concentration of acyclovir in the plasma. Oral acyclovir was well tolerated.